2023
DOI: 10.1001/jamanetworkopen.2023.5428
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean Delivery Trends Among Patients at Low Risk for Cesarean Delivery in the US, 2000-2019

Abstract: ImportanceReducing rates of unnecessary cesarean deliveries is both a national and a global health objective. However, there are limited national US data on trends in indications for low-risk cesarean delivery.ObjectiveTo determine temporal trends in and indications for cesarean delivery among patients at low risk for the procedure over a 20-year period.Design, Setting, and ParticipantsThis cross-sectional study analyzed 2000 to 2019 delivery hospitalizations using the National Inpatient Sample. Births at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Increased rates of abnormal intrapartum fetal monitoring can be expected owing to prolongation of labor, particularly the second stage, justifying both the finding of increased risk of cesarean delivery for nonreassuring fetal status and lower rate of labor arrest in the second phase of the study by Frappaolo and colleauges. 1 On the maternal side, the benefits of prolonged labor on the reduction of cesarean delivery rates should be cautiously weighed against long-term risks of obstetric anal sphincter injury and pelvic floor dysfunctions, as well as uterine atony and postpartum hemorrhage.…”
Section: + Related Articlementioning
confidence: 99%
See 4 more Smart Citations
“…Increased rates of abnormal intrapartum fetal monitoring can be expected owing to prolongation of labor, particularly the second stage, justifying both the finding of increased risk of cesarean delivery for nonreassuring fetal status and lower rate of labor arrest in the second phase of the study by Frappaolo and colleauges. 1 On the maternal side, the benefits of prolonged labor on the reduction of cesarean delivery rates should be cautiously weighed against long-term risks of obstetric anal sphincter injury and pelvic floor dysfunctions, as well as uterine atony and postpartum hemorrhage.…”
Section: + Related Articlementioning
confidence: 99%
“…delivery rates across the study period showed a decrease, with a change in the frequency of the various indications for cesarean delivery over time, with decreasing rates of labor arrest widely exceeding the increasing rates of nonreassuring fetal status. 1 The authors note that the use of administrative data is a major limitation of their study, because it includes the risks of diagnostic discrepancy with clinical files and a lack of standardization of intrapartum diagnoses among different centers, both of which are challenging in similar studies and represent nonnegligible sources of bias and heterogeneity. However, these limitations do not hinder the extensive merit and importance of the present study.…”
mentioning
confidence: 99%
See 3 more Smart Citations